2022
DOI: 10.3390/biom12040575
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Alters the Proteome Profile and Enhances the Angiogenic Potential of Dental Pulp Stem Cell-Derived Exosomes

Abstract: Dental pulp stem cells (DPSCs) and their exosomes (Exos) are effective treatments for regenerative medicine. Hypoxia was confirmed to improve the angiogenic potential of stem cells. However, the angiogenic effect and mechanism of hypoxia-preconditioned DPSC-Exos are poorly understood. We isolated exosomes from DPSCs under normoxia (Nor-Exos) and hypoxia (Hypo-Exos) and added them to human umbilical vein endothelial cells (HUVECs). HUVEC proliferation, migration and angiogenic capacity were assessed by CCK-8, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…However, the effects of hypoxia on the therapeutic potential of DPSC-sEV remain largely unknown. Our recent study revealed that hypoxia-induced DPSC-sEV have enhanced angiogenic potential through the enrichment of LOXL2 compared with control DPSC-sEV [ 26 ]. Here, we showed that hypoxia promotes the release of sEV from DPSCs, which is in line with recent studies about the effects of hypoxia on the release of exosomes in tumor cells and umbilical cord MSCs [ 42 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of hypoxia on the therapeutic potential of DPSC-sEV remain largely unknown. Our recent study revealed that hypoxia-induced DPSC-sEV have enhanced angiogenic potential through the enrichment of LOXL2 compared with control DPSC-sEV [ 26 ]. Here, we showed that hypoxia promotes the release of sEV from DPSCs, which is in line with recent studies about the effects of hypoxia on the release of exosomes in tumor cells and umbilical cord MSCs [ 42 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that the proteomics of hypoxia-preconditioned DPSC-derived sEV were significantly different from those of control DPSC-sEV. More importantly, hypoxia-preconditioned DPSC-derived sEV showed increased angiogenic potential [ 26 ]. However, whether DPSC-sEV produced under hypoxic conditions exert better therapeutic effects on inflammatory osteolysis by inhibiting the macrophage inflammatory response and osteoclastogenesis remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The ECs are activated during collateral artery formation (arteriogenesis) (18), resulting in their proliferation, migration, and differentiation into tubular structures. The surrounding tissues wrap around the ECs to form vascular walls, and vascular networks coincide, initiating the collateral circulation (19)(20)(21). Researchers have a contrary opinion regarding the role of hypoxia in arteriogenesis.…”
Section: Mir-195-3p Inhibitor Rescued the Apoptosis Of Hypoxia Injure...mentioning
confidence: 99%
“…Furthermore, hypoxia partially altered the proteomic profile of odontogenic EVs and increased their vasculogenesis capacity, and researchers hypothesized that LOXL2 could be involved in Hypo-EVs mediated angiogenesis (Li, Xian, et al, 2022). In terms of cell apoptosis, hDPSC-apoVs activated ECs autophagy signaling through the transfer of mitochondrial Tu translation elongation factor (TUFM),…”
Section: Enhance Angiogenesismentioning
confidence: 99%
“…Pulp tissue is exposed to ischemic–hypoxic environment due to the rigid dentin wall and the narrow apical foramina (Li, Wu, et al, 2022; Li, Xian, et al, 2022). At present, the biological effects of DSC‐EVs under hypoxia, as well as the specific molecular mechanisms regulating angiogenesis, have become research priorities.…”
Section: The Possible Molecular Mechanisms Of Odontogenic Evs In Dent...mentioning
confidence: 99%